'Digital Dancing' – "Can you see, what I feel" – An exploration of the physical 'experience' of dance for Parkinson's through 3-dimensional motion analysis. (August 2020) - Hulbert, Sophia; Fullam, James; Hunt, Christopher; Goodwin, Victoria A
Highlights: Research show dancing has a positive impact on the lives of people living with Parkinson's. Current methods of evaluation fail to appreciate the interactive, physical and psychosocial impact of dance. Novel integrated mixed methods enable appreciation of both the physical effects and the lived experience of dance. Abstract: Background: : Parkinson's is a common, progressive, neurodegenerative movement disorder of the central nervous system. Research has consistently shown that dancing can have a positive impact on the lives of people living with Parkinson's (PwP). PwP who dance report that current measurement of the effects fails to appreciate the multifactorial presentation of the condition as well as the biopsychosocial potential of dance holistically. Aim: : To explore the feasibility of combining measurements of whole-body movement using 3-dimensional motion analysis with the lived experience of dance for PwP, to see if it is possible to 'see (measure)' what PwP say they 'feel (experience)' when dancing, in a 'mind/body approach' Method: : Thirteen PwP and ten Carers took part in three community delivered 'Parkinson's Dance Science' classes followed by focus group reflection. Three PwP wore a 3-dimensional, motion capture suit that recorded whole-body movement throughout the class and were interviewed about their experiences. Data were analysed using a 'Convergent Parallel' mixed methods design, mapping participant's experiences and reflections over six biomechanical movement variables. Results: : Quantitative results indicate that it is possible to use 3-dimensional motion capture to measure biomechanical change during and following dance in PwP but the amount and direction of change was different for each participant. Qualitative results showed PwP felt the methods were feasible and reported a positive immediate and long-term effect of dance in a complete 'mind/body experience'. The sample size did not permit further analysis, but areas of development suggest it may not be the change in physical ability that is important, but more the perception of change following dance that is unique to each individual. Thus single measures of the effects of dance for PwP are likely to be insufficient when trying to understand the effect holistically. Conclusion: : A 'Convergent Parallel' mixed methods research design, mapping the experience of dance for PwP ('what I feel') and their peers against biomechanical change ('what you see') following dance is feasible. Further research is required to develop the method with a larger sample to truly begin to understand the potential and effects of dance for PwP.